Variability of aerosol particle concentrations from tyre and brake wear emissions in an urban area - Mailin Samland; Ronny Badeke; David Grawe; Volker Matthias (Atmospheric Environment: X)
Air pollution is a risk to human health, especially in urban areas. While exhaust emissions from road traffic have decreased over the last decades, non-exhaust emissions remain and tend to increase. In this study, tyre and brake wear emissions are quantified applying a bottom-up model for the city of Hamburg in 2018. Their dispersion and contribution to total particulate matter (PM) concentrations are investigated with the urban scale chemistry transport model EPISODE-CityChem. For this purpose, EPISODE-CityChem has been extended to include six new particle components. These are tyre and brake wear in three size classes, PM2.5, PM2.5−10 and PM10+, each.PM concentrations at traffic stations show a higher monthly mean contribution of tyre and brake wear to the total PM2.5 and PM10 than at urban background stations. The sum of airborne tyre and brake wear can locally exceed annual mean concentrations of 10 µgm−3, with the highest concentrations in the inner city of Hamburg.The contribution of tyre and brake wear to the total particle concentrations varies locally and seasonally, which could be a difficulty in adhering to the recommended guideline values for particle concentrations.The results of this study can be transferred to other large European cities with high traffic volumes and can help to understand the problem’s scope, as measurements rarely differentiate between particles caused by exhaust vs. non-exhaust emissions.